WAYS OF TEACHING PHRASEOLOGICAL UNITS (Proceedings of International Educators Conference, 2023)
Phraseological units are a fundamental part of language learning and communication. They are groups of words that have a fixed meaning and cannot be understood by the literal sense of each word. Teaching phraseological units at school is crucial because it helps students improve their language skills, enrich their vocabulary, and communicate more effectively. In this article, we will explore the importance of teaching phraseological units, the different types of phraseological units, and some useful phraseological units for pupils.